2018
DOI: 10.1002/jcp.26947
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of smoothened in breast cancer cells reduces CAXII expression and cell migration

Abstract: Breast cancer (BC) relapse and metastasis are the leading cause of death and, together with drug resistance, keep mortality still high. The Hedgehog (Hh) pathway is expressed during embryogenesis, organogenesis and in adult tissue homeostasis and its aberrant activation is often associated with cancer. Carbonic anhydrase (CA) enzymes are important during development; they play a key role in controlling several cellular mechanisms, such as pH regulation, survival, and migration, and they are aberrantly expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Recently, our research group discovered a correlation between the Hh pathway and CAXII on breast cancer cell migration [ 36 ]. The Hh pathway was already explored in melanoma [ 49 , 50 ], however its involvement in CAs modulation has not been investigated yet.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, our research group discovered a correlation between the Hh pathway and CAXII on breast cancer cell migration [ 36 ]. The Hh pathway was already explored in melanoma [ 49 , 50 ], however its involvement in CAs modulation has not been investigated yet.…”
Section: Resultsmentioning
confidence: 99%
“…CAXII has been recently proposed as a possible target for anticancer therapy [ 31 ] and novel and specific inhibitors of this enzyme, along with CAIX, have been recently identified [ 33 ]. Furthermore, we have recently reported that CAXII expression is regulated by the Hh pathway in breast cancer, indicating that this enzyme plays a potential role in breast cancer cell migration and invasiveness [ 36 ]. We here report, for the first time, that the Hh pathway is involved in the modulation of CAXII also in melanoma cells, in particular, in a moderate aggressive melanoma cell line and, more interestingly, in hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Guerrini et al found that the SHH signaling pathway regulates breast cancer cell migration and invasion through carbonic anhydrase (CA) II [126]. SHH pathway activation affects breast cancer metastasis [127].…”
Section: Shh In Breast Cancermentioning
confidence: 99%